WRC Vodafone Rally de Portugal fostering tourism development - Liberato, Dália (2023)
Events influence the destinations that host them. It was therefore considered interesting to analyze the influence of the Portuguese Rally sports’ event at Porto. This research aims at evaluating the role of the Rally of Portugal in Porto as a tourism destination. It aims to identify the stakeholders’ opinion regarding the impact of the Rally of Portugal on tourism demand in the city of Porto, to evaluate the impact of the Rally of Portugal in Porto as a destination, to identify the conditioning components of the realization of the Rally of Portugal, and to perceive strategies to be applied in future editions, in less secure contexts. A qualitative methodology was used for data collection, through the convenience sampling method, according to the availability of the participants. Individual semi-structured online interviews using the Zoom platform were applied to event organizers, a former pilot, and a pilot of the event. It was verified that the Porto Street Stage, stage of the Rally of Portugal that takes place in the city of Porto, presents many positive impacts for the destination, which in the perspective of the organization include the international projection of the city of Porto (through the presence of the specialized international press), with passage of the circuit by the main urban tourism resources, increase of income, complementary social programs to the event, and pride of the resident community, regarding the reception of the event. From this perspective, the fact that the event was not held in 2020 due to the SARS-CoV-2 virus was significantly reflected in the absence of revenue at the destination, with a negative impact in organizational terms, given the advanced state of this process when the event was canceled, in particular the stages of route definition, budgeting, and communication/dissemination, with the involvement of specialized teams.